2022
DOI: 10.1155/2022/9369387
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Antibacterial Properties of Fontitrygon margarita (Günther, 1870) Liver Oil

Abstract: Objective. The aim of this study was to determine the chemical characteristics and antibacterial activity of Fontitrygon margarita liver oil against the bacteria responsible for food poisoning. Methods. Oils were extracted from F. margarita liver using two methods (exudation and cooking-pressing) and analyses by Fourier transform infrared (FTIR) spectroscopy. Quality indexes were determined using standard methods and the fatty acid profile was carried out by gas chromatography with a flame ionization detector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 18 publications
(19 reference statements)
2
11
2
Order By: Relevance
“…Simo et al also found that oil from F. margarita liver had activity against bacteria responsible for food-borne illnesses, with exudation-obtained oil being more active than cooking-pressed oil. Furthermore, the nanoemulsion of this oil exhibited better activity than the crude oil [21]. Te antimicrobial activity of these oils could be explained by the presence of signifcant amounts of PUFA including DHA, EPA, linolenic acid, arachidonic acid, palmitoleic acid, and oleic acid [35].…”
Section: Referencesmentioning
confidence: 91%
See 4 more Smart Citations
“…Simo et al also found that oil from F. margarita liver had activity against bacteria responsible for food-borne illnesses, with exudation-obtained oil being more active than cooking-pressed oil. Furthermore, the nanoemulsion of this oil exhibited better activity than the crude oil [21]. Te antimicrobial activity of these oils could be explained by the presence of signifcant amounts of PUFA including DHA, EPA, linolenic acid, arachidonic acid, palmitoleic acid, and oleic acid [35].…”
Section: Referencesmentioning
confidence: 91%
“…In the study conducted by Manz Koule et al [28] on Ethmalosa fmbriata fllet, the Bligh and Dyer method was used to extract oil, which showed low SaV (96.04 mgKOH/g) compared to standards but respected the standards for AcV (1.04 mgKOG/g), TaV (1.13 µmol MDA/kg), PeV (1.28 meqO 2 /kg), and AnV (0.76). Noutsa et al [21] extracted oils from Fontitrygon margarita liver using cooking-pressing and exudation methods and achieved results that were within the standards for AcV (2.15-2.30 mgKOH/mg), TaV (2.36-3.20 µmol MDA/kg), PeV (3.34-3.57 meqO 2 /kg), AnV (2.85-3.32), and Totox value (9.04-10.21) for both methods. Te IiV did not signifcantly vary according to the extraction method (102.42-106.65 g I 2 /100 g).…”
Section: Oil Content and Physicochemical Characteristics Of Fish Oils...mentioning
confidence: 99%
See 3 more Smart Citations